Broadening the Scope of Biocatalysis in Sustainable Organic Synthesis. Issue 13 (1st April 2019) - Sheldon, Roger A.; Brady, Dean
Abstract: This Review is aimed at synthetic organic chemists who may be familiar with organometallic catalysis but have no experience with biocatalysis, and seeks to provide an answer to the perennial question: if it is so attractive, why wasn't it extensively used in the past? The development of biocatalysis in industrial organic synthesis is traced from the middle of the last century. Advances in molecular biology in the last two decades, in particular genome sequencing, gene synthesis and directed evolution of proteins, have enabled remarkable improvements in scope and substantially reduced biocatalyst development times and cost contributions. Additionally, improvements in biocatalyst recovery and reuse have been facilitated by developments in enzyme immobilization technologies. Biocatalysis has become eminently competitive with chemocatalysis and the biocatalytic production of important pharmaceutical intermediates, such as enantiopure alcohols and amines, has become mainstream organic synthesis. The synthetic space of biocatalysis has significantly expanded and is currently being extended even further to include new‐to‐nature biocatalytic reactions. Abstract : You've come a long way, baby : Biocatalysis has come a long way in the last two decades, facilitated by advances in molecular biology, especially in oxidative reactions. Civilization's need for sustainable and green chemistry, enabled by new techniques, will ensure permeation of biocatalytic reactions into new areas of industrial chemistry.